Empowerment and Accountability in difficult settings: What are we learning? - and Gaventa, John; Oswald, Katy (IDS, 2019)
Empowerment and Accountability in Difficult Settings: What Are We Learning? Key Messages Emerging from the Action for Empowerment and Accountability Programme Empowerment and accountability have long been part of the international development vocabulary and a core part of governance, social development and civil society programmes. Yet, much of what has been learnt about these approaches has been drawn from studies in somewhat stable, open and middle-income places around the world. Less is known about how empowerment and accountability are achieved through social and political action in more difficult settings – those faced by institutional fragility, conflict, violence, and closing civic space. This document highlights key messages emerging from the work of the Action for Empowerment and Accountability Research Programme (A4EA), and the implications for how donors, policy makers and practitioners support strategies for empowerment and accountability in fragile, conflict and violence affected settings (FCVAS). Our eight key messages have strong implications for the theories of change used for effective programming in the field.